Educating international nurses: curricular innovation through a bachelor of science in nursing bridging program. - Coffey S (Nurse Educator, 2006)
A curricular innovation was designed to provide internationally educated nurses with access to nursing licensure and employment. Through a program that includes professionally relevant English language support, mentorship, academic upgrading, workplace experiences, and clinical skills support, a mechanism has been created for internationally educated nurses to earn a bachelor of science in nursing degree and overcome barriers to practicing their profession.